Joining and welding with a nanothermite and exothermic bonding using reactive multi-nanolayers – A review. (March 2022) - Dombroski, David M.B.; Wang, Anqi; Wen, John Z.; Alfano, Marco
Abstract: Joining and welding using a nanothermite is a matter of exercising control to introduce the energy needed to perform the weld at a required rate and duration sufficient to reach the joining location and produce the required phase change. This focus is the main drive herein with key properties of exothermic joining/welding discussed from the two perspectives of having the energetic source located internally or externally to the joint. Further works on reactive bonding are also investigated, and some emerging applications are discussed, as well as limitations of current solutions summarily presented, and future development potential is provided as closure.